Predicting mental health after living kidney donation: The importance of psychological factors. Issue 3 (21st January 2016) - Timmerman, Lotte; Timman, Reinier; Laging, Mirjam; Zuidema, Willij C.; Beck, Denise K.; IJzermans, Jan N. M.; Busschbach, Jan J. V.; Weimar, Willem; Massey, Emma K.
Abstract : Objectives: Living donor kidney transplantation offers advantages to the patient, however involves risks to the donor. To optimize donors' mental health after donation, we studied the influence of psychological factors on this outcome. Potential predictors were based on models of Lazarus (1999 ) and Ursin and Eriksen (2004 ) that describe predictors of mental health mediated by stress. Design: Prospective design. Methods: Living kidney donors ( n  = 151) were interviewed before donation and completed questionnaires 2.5 months before and 3 and 12 months post‐donation. Using multilevel regression models, we examined whether appraisals, expectations, knowledge, social support, coping, life events, and sociodemographic characteristics predicted psychological symptoms and well‐being and whether these relationships were mediated by stress. Results: A greater increase in psychological symptoms over time was found among donors without a partner. Younger age, lack of social support, expectations of interpersonal benefit, lower appraisals of manageability, and an avoidant coping style were related to more psychological symptoms at all time points. The latter three were mediated by stress. No religious affiliation, unemployment, history of psychological problems, less social support, expectations of negative health consequences, and less positive appraisals were related to lower well‐being at all time points. Conclusions: This study identified indicators of a lower mental health status among living kidney donors. Professionals should examine this profile before donation and the need for extra psychological support in relation to the number and magnitude of the identified indicators. Interventions should be focused on the changeable factors (e.g., expectations), decreasing stress/psychological symptoms, and/or increasing well‐being. Statement of contribution What is already known on this subject? Until now, research on psychological outcomes after living kidney donation revealed that mental health remained the same for the majority of living kidney donors, while mental health improved or deteriorated for a minority after donation. In reaction to these findings, many psychosocial screening guidelines have been developed for potential donors; however, the components of these guidelines are based on professional opinions and experience rather than on longitudinal empirical data. There is a lack of research that identifies pre‐donation donor characteristics that are related to a lower mental health among donors. Such studies are essential in order to tailor psychosocial support during the donation process. What does this study add? Components that are mostly included in psychosocial screening guidelines for potential living kidney donors are not predictive of deterioration, nor increase, in mental health after donation, except for the lack of a partner. Therefore, there is little evidence on the necessity of rejecting potential donors based on these psychological criteria. The following psychological risk factors are predictive of the absolute level of donors' mental health during the donation process: A history of psychological problems, expectations of interpersonal benefit and negative health outcomes, an avoidant coping style, lack of social support, appraisals of the donation process as an unmanageable and/or negative event, a younger age, no religious affiliation, and unemployment. We argue that potential donors should not be rejected for donation based on these factors, but the indicators should be used to identify donors who might be in need for more psychological support.